Pump It Up and Zig Zag Run Training Improve Children Agility Age 7-8 Years Old - Kurniani Fatma Hardini; Gadis Meinar Sari; Choesnan Effendi (Universitas STRADA Indonesia, 2020)
This study used experimental research, with a Randomized Pre and Post Test Group Design. This study consisted of 3 groups: the Pump It Up group, the Zig Zag Run game group, and the Shuttle Run game control group with a sample of each group of 10. The Agility Illionis Test was chosen as the agility test instrument. The exercise was done three days a week for four weeks. Anova test results showed that there was a significant effect of Pump It Up and Zig Zag Run exercises on agility with indigo p <0.05, and LSD test showed there were differences in Pump It Up with Ziz Zag Run, there were differences in Pump It Up and Zig Zag Run with indigo p <0.05. The conclusion of this research was that Pump It Up and Zig Zag Run exercises increase agility